PELATIHAN MANAJEMEN KEUANGAN BAGI PELAKU USAHA TERASI DESA LERAN KECAMATAN SLUKE KABUPATEN REMBANG SEBAGAI PEMBEKALAN KETERAMPILAN BERWIRAUSAHA - Agustina Widodo; Syaiko Rosyidi (Buletin Abdi Masyarakat, 2021)
This community service program aims to provide skills for shrimp paste business actors in Leran Village, Sluke District, Rembang Regency. The problems faced by the shrimp paste business group are: (1) Low understanding of the importance of financial management, (2) Low implementation of good financial administration, (3) Irregular financial administration. The solutions offered are in accordance with the priority issues agreed upon with partners are: (1) Organizing financial management and financial administration training, (2) Providing training in financial management and financial administration training. The output targets of the shrimp paste business community service activities are: (1) The business group has financial administration documentation (2) The business group has regular and complete bookkeeping, so that its business financial circulation can be seen (3) The business group is able to compile its own financial statements. (4) Scientific publication and seminar results.Keywords: Financial Management, Training and Mentoring